2018
DOI: 10.1007/s12928-018-0543-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tissue characterization for in-stent restenosis with optical coherence tomography during excimer laser coronary angioplasty

Abstract: We aimed to evaluate the impact of tissue characterization for in-stent restenosis (ISR) with optical computed tomography (OCT) during excimer laser coronary angioplasty (ELCA) in the drug-eluting stent (DES) era. The effect of ELCA for ISR according to differences in tissue characteristics is unclear. Fifty-three ISR lesions (7 bare metal stents and 46 drug-eluting stents) were treated with an ELCA catheter. After ELCA, balloon dilatation with either the scoring or non-compliant balloons was conducted. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In another study with 42 patients with ISR, Miyazaki et al 13 compared ELCA+scoring balloon+DEB vs scoring balloon+DEB and found similar long-term angiographic and clinical results. Hashimoto et al 14 used OCT to characterise the underlying tissue in 53 ISR lesions treated with ELCA+DEB and found that the minimal lumen area after ablation was larger in mixed lesions than in those with a homogeneous pattern. Alternatively, Ishihara et al 15 compared results of 47 ISR lesions treated with ELCA+DEB with 161 ISR lesions treated with DEB only.…”
Section: Previous Studies Systematic Use Of Elca In Patients With Isrmentioning
confidence: 99%
“…In another study with 42 patients with ISR, Miyazaki et al 13 compared ELCA+scoring balloon+DEB vs scoring balloon+DEB and found similar long-term angiographic and clinical results. Hashimoto et al 14 used OCT to characterise the underlying tissue in 53 ISR lesions treated with ELCA+DEB and found that the minimal lumen area after ablation was larger in mixed lesions than in those with a homogeneous pattern. Alternatively, Ishihara et al 15 compared results of 47 ISR lesions treated with ELCA+DEB with 161 ISR lesions treated with DEB only.…”
Section: Previous Studies Systematic Use Of Elca In Patients With Isrmentioning
confidence: 99%